Development of Post-Treatment Facial Palsys in Patients with Vestibular Schwannoma: Retrospective Study 2003 to 2021, Puebla, Mexico - Genchi Gatica , Roberto; Contreras Palafox , Gabriel Alejandro; Osorio-Espinoza, Angélica (Revista Médica de Risaralda, 2025)
Introduction: Vestibular schwannomas are the most common benign intracranial tumors of the cerebellopontine angle, it is a tumor that grows from schwann cells and affects the eighth and seventh cranial nerve. Radiotherapy is the direct application of high doses of radiation directed at the lesion, resulting in an alternative treatment to neurosurgery. Objective: To determine the number of clinical files of patients with vestibular schwannoma who developed facial palsy after treatment with single-dose, hypofractionated radiosurgery and neurosurgery. Material And Methods: The study was performed by analyzing the clinical records of the "Manuel Velasco Suárez" National Institute of Neurology and Neurosurgery, in which the results of post-treatment facial palsy were found. Results: The sample is composed of 137 clinical records in total, of which 90 were women and 47 were men, the average age between each group was 44.12 ± 14 years for single dose, 53.73 ± 11.16 years for hypofractionation and 38.85 ± 14.36 years for neurosurgery. It was possible to determine that the patients who developed facial palsy post treatment with neurosurgery were 44.11% of the total, the patients treated with hypofractionated dose radiosurgery had 30.7% and of the patients treated with single dose radiosurgery only 23.37% developed facial paralysis. Conclusion: Patients treated with neurosurgery have a high percentage with development of facial palsy, followed in incidence by patients with vestibular schwannoma with hypofractionated dose radiosurgery treatment and finally patients treated with single dose radiosurgery.